Reading materials and reading motivation among TESL students in UiTM Shah Alam, Malaysia / Nur Syamira Yusoff Lutefi - Yusoff Lutefi, Nur Syamira (Faculty of Education, 2014)
Reading is the most important component in acquiring the language Danelian (1997) & Mokatsi (2005). The aim of this study was to investigate the students' preferences of reading materials and reading motivation. In addition, this study also conducted to investigate the relationship between students' preferences of reading materials and students' level of reading motivation. This employed mixed-method design encompassing both quantitative and qualitative approaches in data gathering and analysis. The study involved 70 respondents that were enrolled in the TESL programme at the Faculty of Education in UiTM, Shah Alam. The findings revealed that the total mean score for the students' reading preferences was 4.5 (SD=1.0). This indicating that the students were more than occasionally read the reading materials. The study also revealed that the total mean score for the students' level of motivation was 4.9 (SD=0.9). This indicated that the students almost frequently motivated to read. Besides that, the study also revealed that students' preferences of reading materials did correlate with the students' levels of reading motivation. The results from qualitative data also revealed that the students' tend to prefer reading academic reading materials for academic purposes only.